The suitability of the orthophoto generated from unmanned aerial vehicle for updating cadastral map and demarcate the boundary mark position / Mimi Sahada Shamsuddin - Shamsuddin, Mimi Sahada (2020)
The Unmanned Aerial Vehicle (UAV) was the best approach in order to acquire the highly accurate data in cadastral surveying by using low cost digital camera. Unmanned aerial Vehicle has a flexibility and efficiency in capturing the area from the low flight altitude. The UAV images widespread radiantly in many fields because of it could save time and cost to conduct the survey. The scope of this research includes the generating orthophoto by using photogrammetry module. The UAV images were processed in the Agisoft Photoscan Software which was able to calibrate the camera itself. Next, the ground control point (GCPs) and verification point (VP) had been marked by using the GNSS module of GPS observation. There are eight ground control point and thirty verification point established around the study area. The verification points were used in verified the accuracy of the UAV images in mapping. The coordinates were obtained from ground survey were compared with the coordinates obtained from the orthophoto in order to calculate the RMSE. The accuracy of orthophoto also could be analyses by performed the pre-identification of boundary mark position on orthophoto. The study area covered the UITM Campus Arau, Arau Perlis. This research was significant in determine the suitability of the orthophoto for updating the cadastral map and demarcate the boundary mark.